An oxygen vacancy defect and chalcogens impurities in earth-abundant lead-free calcium zirconate perovskite for non-toxic solar cells: First-principles calculations. (December 2022) - Dahbi, S.; Mouhib, B.; Tahiri, N.; El Bounagui, O.; Mounkachi, O.; Ez-Zahraouy, H.
Abstract: The effects of an oxygen vacancy (Ov), and chalcogens impurities on electronic, optical properties, thermodynamic stability, and photocatalytic hydrogen production form water splitting ability of non-toxic lead-free calcium zirconate perovskite CaZrO3 are investigated using first-principles calculations-based Density Functional Theory and LDA+TB-mBJ functional. It is found that an Ov itself in CaZrO3 compound results of free electrons inside the unoccupied states in CB which changed the type of electrical conductivity from p to n-type. Besides, the wide forbidden band energy of CaZrO3 was effectively reduced when chalcogens impurities doped CaZrO3 with the presence of an Ov. Furthermore, the optical properties show that the percentage of the transmittance reduced while the absorption coefficient's percentage increased along the visible spectrum in all structures having an Ov, suggesting that Ov creates free charge carriers in the CaZrO3 compound. In Addition, the formation energy confirms that all studied structures are thermodynamically stables. Finley, S/Se@OI/OII/OIII+Ov structures are promising photocatalysts to drive water splitting reactions as they are distinguished by their appropriate forbidden bands, visible light absorption, and band edge positions. We believe that our study could be used to give CaZrO3 the opportunity to be used as a semiconductor for photovoltaic and photocatalytic applications. Graphical Abstract: ga1